Toward the Practice of Social Innovation for the Common Good: An Integration of “Teaching-Research-Service” - Han, I.; Hou, Sheng-Tsung (Social Innovation and Business in Taiwan, 2016)
“Many suppliers and users of social research are dissatisfied, the former because they are not listened to, the latter because they do not hear much they want to listen to” (Lindblom & Cohen, 1979: 1). As mentioned in Chapter 1 of this book, the recent events of global financial crisis and a series of Occupy Wall Street protests have raised reflections of business management education on MBA trainings. The question of whether management research and education can be a facilitator toward events that would eventually destroy the world economy or a facilitator toward achieving social value and human glory has been raised with those reflections. MBA graduates should not be used as profiting tools for big corporations anymore. Moreover, the separation between management theory and industry practice has, for a long time, caused a dilemma with regard to the difficulties inherent in dialogue between academia and industry. There have been urgent calls to embody management research into applicable industry knowledge in order to minimize the gap in between the two (Anderson, Herriot, & Hodgkinson, 2001; Rynes, Bartunek, & Daft, 2001; Van de Yen & Johnson, 2006).
Keywords: Asie; Réservé UdeM